2010
DOI: 10.1093/icesjms/fsq174
|View full text |Cite
|
Sign up to set email alerts
|

Ocean surface characteristics influence recruitment variability of populations of northern shrimp (Pandalus borealis) in the Northwest Atlantic

Abstract: Ouellet, P., Fuentes-Yaco, C., Savard, L., Platt, T., Sathyendranath, S., Koeller, P., Orr, D., and Siegstad, H. 2011. Ocean surface characteristics influence recruitment variability of populations of northern shrimp (Pandalus borealis) in the Northwest Atlantic. – ICES Journal of Marine Science, 68: 737–744. Remotely sensed data were used to derive simple ecosystem indicators for four regions of the Northwest Atlantic to test the hypothesis that sea surface temperatures (SSTs) and spring phytoplankton bloom c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 28 publications
0
15
1
Order By: Relevance
“…Previous authors have speculated that the most important effect of temperature might be on timing of the hatch relative to the timing of the plankton bloom (Stickney & Perkins 1977, Richards et al 1996. Close temporal matches between hatch timing and the spring phytoplankton bloom have been shown for several northern shrimp populations across the North Atlantic (Koeller et al 2009, Ouellet et al 2011; however, the GOM hatch was an exception to this pattern (Koeller et al 2009). In our analysis, PC2 (primarily autumn bottom temperature) was not as important as PC1 (spring temperatures), suggesting that hatch timing and/or brood parasitism may be less critical than a variety of potential spring temperature effects.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Previous authors have speculated that the most important effect of temperature might be on timing of the hatch relative to the timing of the plankton bloom (Stickney & Perkins 1977, Richards et al 1996. Close temporal matches between hatch timing and the spring phytoplankton bloom have been shown for several northern shrimp populations across the North Atlantic (Koeller et al 2009, Ouellet et al 2011; however, the GOM hatch was an exception to this pattern (Koeller et al 2009). In our analysis, PC2 (primarily autumn bottom temperature) was not as important as PC1 (spring temperatures), suggesting that hatch timing and/or brood parasitism may be less critical than a variety of potential spring temperature effects.…”
Section: Discussionmentioning
confidence: 69%
“…In a meta-analysis of 9 northern shrimp populations, Worm & Myers (2003) found that biomass was directly influenced by predation pressure in most populations, but not by ocean temperature. Recruitment and larval survival were negatively correlated with SST in the Gulf of St. Lawrence (Ouellet et al 2007), but in later studies, the relationship was not significant (Ouellet et al 2011). However, positive correlations between recruitment and temperature have been seen in the Barents Sea (Aschan & Ingvaldsen 2009) and off West Greenland (Wieland 2005), both near the species' northern limit.…”
Section: Discussionmentioning
confidence: 89%
“…Although cod predation has an impact on northern shrimp biomass, other factors, such as fishing (Savenkoff et al 2007), ocean climate variability (Wieland 2005, Ouellet et al 2011, size of areas of suitable habitat and larval transport (Koeller 2000) may also be important factors in regulating shrimp abundance. Further work is needed to evaluate how northern shrimp may respond to changes in predator abundances in relation to other factors, such as temperature, other ocean climate variables, abundance of other prey, and the distribution of predators and prey.…”
Section: Discussionmentioning
confidence: 99%
“…However, the overall effect of lower temperatures on recruitment is positive (Marcello et al 2012), implying that positive effects on early survival dominate recruitment dynamics. In contrast, northern shrimp off West Greenland benefit from warmer surface layer temperatures, presumably due to enhanced food availability for the larvae, as long as bottom temperatures are also warmer to ensure a match between the time of hatching and the plankton bloom (Koeller et al 2009, Ouellet et al 2011, Wieland & Siegstad 2012.…”
Section: Major Findingsmentioning
confidence: 99%